TINJAUAN YURIDIS TERHADAP TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA BADAN LINGKUNGAN HIDUP KABUPATEN LANGKAT T.A. 2011 (Studi Putusan No: 51/PID_SUS-TPK/2015/PN MDN) - Rahmayanti Rahmayanti (Universitas Islam Sumatera Utara, 2019)
Abstrack This study aims to determine the regulation of corruption. Corruption in Indonesia is increasingly widespread seen from who the perpetrators are, how they commit corruption, and how much the state’s losses incurred. Indonesia's Corruption Watch (ICU) notes that the perpetrators of the most corruption are from civil servants (PNS) and they are in the top rank. This study aims to find out how the civil servants commit corruption in the procurement of government goods and services, and how far the mode or method affects the judge in making a decision. This study uses a normative method. The civil servants commit corruption in different ways or procedures with special characteristics. Putting personal interests above the community ones and something entrusted to them is not carried out properly is called modus operandi. The modus operandi carried out by civil servants in the procurement of government goods and services occurs in all stages of procurement and implementation of the modus operandi, and it also influences the criminal convictions, especially in the high and lower levels of criminal behavior; the more despicable the crime is, the higher the speech.1 Based on the results of this study, it can be concluded that three problems that often occur in the process of procurement of goods and services. Key Words: Modus Operandi, Corruption, Civil Servants, Judge’s Decision